A new mound-building biota from the lower Carboniferous of Alabama. (May 2020) - Kopaska-Merkel, David C.; Haywick, Douglas W.; Keyes, Richard G.
Abstract: A small (1.2 m) columnar carbonate mound in shaley strata equivalent to the Hartselle Sandstone (lower Serpukhovian) near Woodville, northeastern Alabama, was built by a consortium of species unlike those of other Carboniferous mounds in the southeastern United States. The mound contains a new problematic microencruster, Aphralysia anfracta new species, along with encrusting bryozoans ( Fistulipora M'Coy, 1849 ), nonskeletal microbes, and other microencrusters, including Aphralysia capriorae Mamet and Roux, 1975, in a carbonate mud matrix. Mound cavities are filled with three generations of carbonate and siliciclastic sediment. Other biotic constituents of the mound include oncoids, sponges (including Pileospongia Rigby, Keyes, and Horowitz, 1979), gastropods, crinoids, a tabulate coral, and coenobionts, including coccoid calcimicrobes. The mound biota, especially the microencrusters, is dramatically different from those of other Serpukhovian mounds that have been described from Alabama (made by various consortia of rugose corals, fenestrate bryozoans, crinoids, sponges, and nonskeletal microbes). Indeed, the Woodville mound extends the range of the lower Carboniferous encruster Aphralysia Garwood, 1914 to North America. UUID: http://zoobank.org/d3988875-a7fb-4382-bd14-b17c083d87ad